What sources of bereavement support are perceived helpful by bereaved people and why? Empirical evidence for the compassionate communities approach - Aoun, S.; Breen, Lauren; White, Ishta; Rumbold, B.; Kellehear, A. (Sage Science Press (UK), 2018)
© 2018, The Author(s) 2018. Aims: To determine who provides bereavement support in the community, what sources are perceived to be the most or least helpful and for what reason, and to identify the empirical elements for optimal support in developing any future compassionate communities approach in palliative care. Design: A population-based cross-sectional investigation of bereavement experiences. Sources of support (informal, community and professional) were categorised according to the Public Health Model of Bereavement Support; most helpful reasons were categorised using the Social Provisions Scale, and least helpful were analysed using inductive content analysis. Setting and participants: Bereaved people were recruited from databases of funeral providers in Australia via an anonymous postal survey (2013–2014). Results: In total, 678 bereaved people responded to the survey. The most frequently used sources of support were in the informal category such as family, friends and funeral providers. While the professional category sources were the least used, they had the highest proportions of perceived unhelpfulness whereas the lowest proportions of unhelpfulness were in the informal category. The functional types of helpful support were Attachment, Reliable Alliance, Social Integration and Guidance. The five themes for least helpful support were: Insensitivity, Absence of Anticipated Support, Poor Advice, Lack of Empathy and Systemic Hindrance. Conclusion: A public health approach, as exemplified by compassionate communities policies and practices, should be adopted to support the majority of bereaved people as much of this support is already provided in informal and other community settings by a range of people already involved in the everyday lives of those recently bereaved. This study has provided further support for the need to strengthen the compassionate communities approach, not only for end of life care for dying patients but also along the continuum of bereavement support.